Efficacy of IncobotulinumtoxinA in the Management of Spasticity and Dystonia in a Pediatric Patient with NUBPL-Related Mitochondrial Disease: A Case Report - Tatiana Kuznetsova (Toxicon, 2026)

Microplastics in the environment: The role of polymer science - Sergey V. Lyulin; Andrey A. Gurtovenko; Francesco Saliu; Paolo Galli; Dinesh Surroop; Aleksander A. Yaroslavov; Svetlana G. Radionova; Tatiana A. Kuznetsova; Jose M. Kenny (Science of The Total Environment, 2025)

Defining left ventricular remodeling using lean body mass allometry: a UK Biobank study - Bruna Gomes; Kristofer Hedman; Tatiana Kuznetsova; Nicholas Cauwenberghs; David Hsu; Yukari Kobayashi; Erik Ingelsson; David Oxborough; Keith George; Michael Salerno; Euan Ashley; Francois Haddad (European Journal of Applied Physiology, 2023)

Cardiac activity in the Mediterranean mussel (Mytilus galloprovincialis Lamarck, 1819) as a biomarker for assessing sea water quality in Boka Kotorska Bay, South Adriatic Sea - MARKO NIKOLIC; TATIANA KUZNETSOVA; SERGEY KHOLODKEVICH; SLADJANA GVOZDENOVIC; MILICA MANDIC; DANIJELA JOKSIMOVIC; IVANA TEODOROVIC (Mediterranean Marine Science, 2019)
This paper presents the results of the sea water quality assessments based on the heart rate monitoring (cardiac responses) of indigenous Mediterranean mussel, Mytilus galloprovincialis. Mussels were sampled from three different sites in the Boka Kotorska Bay varied on anthropogenic pressure. Heart rate recovery time (Trec)and coefficient of variation of heart rate (CVHR) were tested in compliance with the standardized test procedure using a short-term reduction of water salinity as stress treatment to study adaptive potential of tested mussels. Results indicate the highest values of both parameters in Port Bijela, Trec = 77.3 ± 7.2 min; CVHR = 10%, indicating that water quality on this site is worse compare to Stoliv and Dobrota. ANOVA performed on results of Trec showed that values on Port Bijela are statistically significant higher compare to Stoliv and Dobrota. The lowest values of Trec are obtained on Stoliv (47.3 ± 3.8 min) what implies good water quality on this location. ANOVA showed that although higher values of Trec were obtained in Dobrota (53.3 ± 4.8 min) compare to Stoliv, those differences are not statistically significant. The proposed express method could help the authorities to plan and carry out contemporary activities to maintain high ecological status of marine coastal areas and to minimize significant risk to animal’s and human health in the case of suddenly occurred emergency situations in the region or none permitted wastewater discharges.

Comprehensive assessments of ecological states of Songhua River using chemical analysis and bivalves as bioindicators - Victoria V. Zarykhta; Zhaohan Zhang; Sergey V. Kholodkevich; Tatiana V. Kuznetsova; Andrey N. Sharov; Yu Zhang; Kai Sun; Miao Lv; Yujie Feng (Environmental Science and Pollution Research, 2019)

Effects of long-term medieval agriculture on soil properties: A case study from the Kislovodsk basin, Northern Caucasus, Russia - Elena Chernysheva; Tatiana Khomutova; Flavio Fornasier; Tatiana Kuznetsova; Alexandr Borisov (Journal of Mountain Science, 2018)

Hepatitis E Virus in Domestic Pigs, Wild Boars, Pig Farm Workers, and Hunters in Estonia - Anna Ivanova; Valentina Tefanova; Irina Reshetnjak; Tatiana Kuznetsova; Julia Geller; Åke Lundkvist; Marilin Janson; Kädi Neare; Kaisa Velström; Pikka Jokelainen; Brian Lassen; Pirje Hütt; et al. (Food and Environmental Virology, 2015)

Ancient mitochondrial DNA and the genetic history of E urasian beaver ( C astor fiber ) in E urope - Susanne Horn; Stefan Prost; Mathias Stiller; Daniel Makowiecki; Tatiana Kuznetsova; Norbert Benecke; Erich Pucher; Anne K. Hufthammer; Charles Schouwenburg; Beth Shapiro; Michael Hofreiter (Molecular Ecology, 2014)
After centuries of human hunting, the E urasian beaver C astor fiber had disappeared from most of its original range by the end of the 19th century. The surviving relict populations are characterized by both low genetic diversity and strong phylogeographical structure. However, it remains unclear whether these attributes are the result of a human‐induced, late Holocene bottleneck or already existed prior to this reduction in range. To investigate genetic diversity in E urasian beaver populations during the H olocene, we obtained mitochondrial control region DNA sequences from 48 ancient beaver samples and added 152 modern sequences from GenBank. Phylogeographical analyses of the data indicate a differentiation of European beaver populations into three mitochondrial clades. The two main clades occur in western and eastern Europe, respectively, with an early Holocene contact zone in eastern Europe near a present‐day contact zone. A divergent and previously unknown clade of beavers from the Danube Basin survived until at least 6000 years ago, but went extinct during the transition to modern times. Finally, we identify a recent decline in effective population size of E urasian beavers, with a stronger bottleneck signal in the western than in the eastern clade. Our results suggest that the low genetic diversity and the strong phylogeographical structure in recent beavers are artefacts of human hunting‐associated population reductions. While beaver populations have been growing rapidly since the late 19th century, genetic diversity within modern beaver populations remains considerably reduced compared to what was present prior to the period of human hunting and habitat reduction.

Phylogeography of lions ( Panthera leo ssp.) reveals three distinct taxa and a late Pleistocene reduction in genetic diversity - ROSS BARNETT; BETH SHAPIRO; IAN BARNES; SIMON Y. W. HO; JOACHIM BURGER; NOBUYUKI YAMAGUCHI; THOMAS F. G. HIGHAM; H. TODD WHEELER; WILFRIED ROSENDAHL; ANDREI V. SHER; MARINA SOTNIKOVA; TATIANA KUZNETSOVA; et al. (Molecular Ecology, 2009)
Lions were the most widespread carnivores in the late Pleistocene, ranging from southern Africa to the southern USA, but little is known about the evolutionary relationships among these Pleistocene populations or the dynamics that led to their extinction. Using ancient DNA techniques, we obtained mitochondrial sequences from 52 individuals sampled across the present and former range of lions. Phylogenetic analysis revealed three distinct clusters: (i) modern lions, Panthera leo ; (ii) extinct Pleistocene cave lions, which formed a homogeneous population extending from Europe across Beringia (Siberia, Alaska and western Canada); and (iii) extinct American lions, which formed a separate population south of the Pleistocene ice sheets. The American lion appears to have become genetically isolated around 340 000 years ago, despite the apparent lack of significant barriers to gene flow with Beringian populations through much of the late Pleistocene. We found potential evidence of a severe population bottleneck in the cave lion during the previous interstadial, sometime after 48 000 years, adding to evidence from bison, mammoths, horses and brown bears that megafaunal populations underwent major genetic alterations throughout the last interstadial, potentially presaging the processes involved in the subsequent end‐Pleistocene mass extinctions.

Susceptibility of the pistachio processionary mothThaumetopoea solitaria to threeBacillus thuringiensis products - Galina Gindin; Tatiana Kuznetsova; A. Protasov; Nitza Saphir; Z. Madar; Z. Mendel (Phytoparasitica, 2008)